An unusual case of cervical fibroid masquerading as ovarian tumor - Neeru Goel; Shikha Seth (Wolters Kluwer Medknow Publications, 2016)
Uterine fibroids are the most common uterine neoplasm of uterus and the female pelvis and the most common indication for hysterectomy worldwide. When the fibroid is large and fills the whole pelvis or is pedunculated, it becomes difficult to differentiate from ovarian mass clinically. Cervical fibroids pose enormous surgical difficulty by virtue of their relative inaccessibility and proximity to the anterior bladder, posterior rectum, and distorting the normal anatomical relationship of pelvic structures. A cervical fibroid especially with degenerative changes mimics an ovarian tumor and poses a clinical dilemma. This case is also exemplified for its rarity and diagnostic difficulty.